(untitled) (Research, Society and Development, 2021)
This work addresses the relationship between the learning process of children and the forms of playfulness in the school environment, with a focus on knowledge for the Early Childhood Education phase and the educational process. It will mention how to use the tools offered by education in the training of these children, and how they are of great value with regard to the development of teaching and learning. This entire process will contribute to a better society, with more qualified people who make a difference in our future. During the development of this article, the importance of working playfulness in teaching was highlighted in a way that any playful activity can count on the interaction of all children in the school environment. participation of each child according to their specificity and dedicating themselves to every result obtained by the child during their education.